PENGEMBANGAN KREATIVITAS ANAK USIA DINI MELALUIORIGAMI - Sumedi P Nugraha (Asian Journal of Innovation and Entrepreneurship, 2013)
The art of paper folding or origami, an activity that is good for stimulatingcreativity and build structured thinking in children. Realizing that the author chose to tryto teach some simple methods of folding paper to children at an early ageat CangkolDuwur hamlet, Lencoh Village, Boyolali. This activity is the author deliberately held giventhe number of small children who look pretty much and yet their activities that stimulatethe motor development and creativity of children being taught here. Because the subjectof this activity is the early age children, this activity is designed with a simple method.Children who follow these events were only asked to see, and then practice togetherand they even may form other patterns if they want to. The allocation of time on thisactivity is 4 hours with 2 times the effective time of the meeting. The results of thismeeting the children become more creative and began to cultivate the mindset ofcreative, innovative and structured since childhood .